2019
DOI: 10.1111/jpn.13283
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chitosan nanoparticle supplementation on growth performance, humoral immunity, gut microbiota and immune responses after lipopolysaccharide challenge in weaned pigs

Abstract: In this study, we aimed to determine the effects of dietary supplementation with chitosan nanoparticles (CNP) on growth performance, immune status, gut microbiota and immune responses after lipopolysaccharide challenge in weaned pigs. A total of 144 piglets were assigned to four groups receiving different dietary treatments, including basal diets supplemented with 0, 100, 200 and 400 mg/kg CNP fed for 28 days. Each treatment group included six pens (six piglets per pen). The increase in supplemental CNP concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 40 publications
4
27
0
1
Order By: Relevance
“…To our knowledge, this is the first study to evaluate the effects of ChNP supplementation with size up to 17 nm in laying hens. These results are consistent with the results reported by Xu et al (2019) who showed that ChNPs might increase the presence of the useful bacterial species and reduce the pathogenic bacterial species. Conversely, Abd El-Naby et al (2019) found that ChNP supplementation in the diet of Oreochromis niloticus leads to the inhibition of the growth of intestinal bacterial assemblies.…”
Section: Microbial Populationsupporting
confidence: 93%
See 2 more Smart Citations
“…To our knowledge, this is the first study to evaluate the effects of ChNP supplementation with size up to 17 nm in laying hens. These results are consistent with the results reported by Xu et al (2019) who showed that ChNPs might increase the presence of the useful bacterial species and reduce the pathogenic bacterial species. Conversely, Abd El-Naby et al (2019) found that ChNP supplementation in the diet of Oreochromis niloticus leads to the inhibition of the growth of intestinal bacterial assemblies.…”
Section: Microbial Populationsupporting
confidence: 93%
“…However, knowledge of the effects of ChNP on laying hens is still relatively limited. These results are agreement with the results reported by Xu et al (2019) found that the addition of 200 or 400 mg/kg diet resulted in insignificant reduced feed intake compared to the control group of weaned pigs at 28 days; however, they reported that feed and weight gain were decreased (P<0.05) when the…”
Section: Laying Performancesupporting
confidence: 93%
See 1 more Smart Citation
“…Chitosan, a naturally occurring bioactive polymer (a copolymer of N-acetyl-D-glucosamine and D-glucosamine) [48] is the most important chitin derivative, and has received increasing attention due to its specific biodegradability by colon bacteria, its well-documented biocompatibility, low toxicity and mutagenic properties [49]. Evidence has shown that chitosan possesses various biological activities, namely antioxidant, antitumor, anti-inflammatory, immunostimulant, wound healing, coadjutant (in aquatic animals), cholesterol-reducing, antibacterial and antifungal properties, and is useful as an active component of the diet for the loss of body fat.…”
Section: Effects Of Chitin and Derivatives On Human Healthmentioning
confidence: 99%
“…Stimulation of IL-6 resulted in a maximal induction of NF-kB activation and NF-kB nuclear translocation [26] . Overall, IL-6 had the in uence on innate and adaptive immune responses, suggesting that dysfunction of its function could promote the progression of chronic diseases [27] . The distribution of EGFR in gastric mucosal epithelial cells was the most.…”
Section: Discussionmentioning
confidence: 99%